ICT Adoption and Use in Costa Rican Export Companies - Mata, Francisco (2015)
We study the ICT adoption and use in Costa Rican export companies based on the results of a field survey. The e-commerce readiness/intensity/ impact model, developed by the Organisation for Economic Cooperation and Development (OECD), was adapted for this research. The results obtained show that, in general, the surveyed companies present low ICT readiness and intensity, with the exception of service companies and microenterprises. Furthermore, there is no evidence of a clear perceived positive ICT impact on the exports taking into account all companies, neither considering their sector or size. Nevertheless, large companies perceive a positive effect, which is consistent with a sustained increase in their export value. Based on the previous results, we discuss factors that might influence the adoption and use of ICT in the export companies and present recommendations to increase its use. In addition, suggestions for further research are presented.